ANALISIS PENINGKATAN KINERJA GURU PADA SEKOLAH SMK ANTARTIKA SURABAYA - Muhammad Nur Efendi; Tutik Winarsih (JURNAL ILMIAH EDUNOMIKA, 2022)
This study aims to determine the improvement of teacher performance at SMK Antartika Surabaya schools and find out what factors affect the improvement of teacher performance at SMK Antartika Surabaya schools. The populations in this study are 31 teachers at SMK Antartika Surabaya, this research uses a qualitative type of research, which is a data collection technique through interviews and observations. Based on the results of this study, it can be concluded that the analysis of improving the performance of teachers of SMK Antartika Surabaya is not on time as there are empty hours in class with an impact on the quality of work from teachers while the Quantity of Work and Cooperation is very good. Keywords : Teacher Performance, Improvement, Vocational School